Highly Controlled Diffusion Drug Release from Ureasil-Poly(ethylene oxide)-Na+-Montmorillonite Hybrid Hydrogel Nanocomposites - Jesus, Celso R.N. [UNESP]; Molina, Eduardo F.; Pulcinelli, Sandra H. [UNESP]; Santilli, Celso V. [UNESP] (American Chemical Society (ACS), 2018)
In this work, we report the effects of incorporation of variable amounts (1-20 wt %) of sodium montmorillonite (MMT) into a siloxane-poly(ethylene oxide) hybrid hydrogel prepared by the sol-gel route. The aim was to control the nanostructural features of the nanocomposite, improve the release profile of the sodium diclofenac (SDCF) drug, and optimize the swelling behavior of the hydrophilic matrix. The nanoscopic characteristics of the siloxane-cross-linked poly(ethylene oxide) network, the semicrystallinity of the hybrid, and the intercalated or exfoliated structure of the clay were investigated by X-ray diffraction, small-angle X-ray scattering, and differential scanning calorimetry. The correlation between the nanoscopic features of nanocomposites containing different amounts of MMT and the swelling behavior revealed the key role of exfoliated silicate in controlling the water uptake by means of a flow barrier effect. The release of the drug from the nanocomposite displayed a stepped pattern kinetically controlled by the diffusion of SDCF molecules through the mass transport barrier created by the exfoliated silicate. The sustained SDCF release provided by the hybrid hydrogel nanocomposite could be useful for the prolonged treatment of painful conditions, such as arthritis, sprains and strains, gout, migraine, and pain after surgical procedures.
Keywords: drug delivery; montmorillonite; nanocomposite; siloxane-polyether; swelling